As relações profissionais no processo de mentoria - Juer, Mariana (2008)
This project intends to better understand the relationship between mentor and mentee in the organizational mentoring processes and the role of mentoring as an actual organizational demand. Therefore this dissertation considered the bibliography on mentoring evolution, the relationships characteristics, how diversity can influence the processes, possible disfunctions and the participants´ roles, considering their expectations and premises. In order to observe these relationships in a real situation, this project investigates the mentees´ expectations and the mentors´ premises regarding the mentoring functions, as well as the investigation on the confidence level existing among the involved in the Whirlpool´s formal mentoring program for young talents. The hypotheses established according to the theory for the case were: H1a: The career functions are considered the most important issue by the mentees in the case studied. Not confirmed. H1b: The career functions are considered the most important issue by the mentors in the case studied. Not confirmed. H1c: The mentees´ expectations are aligned to the mentors´ premises, regarding the mentoring functions. Not confirmed. H2: Confidence is present among the program´s participants. Confirmed. H3: The expectations among the mentees vary according to the gender regarding the mentoring functions. Confirmed. H4: The program´s relationships are healthful. Confirmed. The dissertation concludes the necessity of complementarity , empathy and confidence between mentor and mentee to assure the relationship success. More than this, a formal program must guarantee that its objectives are clear to all the participants in order to align all expectations and premises. Additionally it must be very well structured to ideally match mentor and mentee, concerning their needs and characteristics as well as to follow up the formed pairs to assure a prompt decision to any kind of disfunctions arised